Wafer‐fused 1300 nm VCSELs with an active region based on superlattice - Sergey Blokhin; Andrey Babichev; Andrey Gladyshev; Leonid Karachinsky; Innokenty Novikov; Alexey Blokhin; Stanislav Rochas; Dmitrii Denisov; Kirill Voropaev; Alexander Ionov; Nikolay Ledentsov; Anton Egorov (Electronics Letters, 2021)
Abstract The 1300 nm range vertical‐cavity surface‐emitting lasers with the active region based on InGaAs/InGaAlAs superlattice are fabricated using molecular‐beam epitaxy and the double wafer‐fusion technique. Lasers with the buried tunnel junction diameter of 5 μm have shown single‐mode CW operation with the output optical power of ∼6 mW at 20°C. Opened eye diagrams are observed up to 10 Gbps.